Invisible Barriers: The Loneliness of School Principals at Turkish Elementary Schools - Korumaz, Mithat (EDUCATION ASSOC SOUTH AFRICA, 2016)
School principals fulfil unique and crucial roles, drawing on their respective experience to react to an increasing number of challenges. They must carry out their roles as school leaders within a context highly charged with emotion. The loneliness of principals at schools urgently requires investigation. Limited details can be found in current academic literature concerning the issue of how principals deal with the issue of loneliness at school. Therefore, the aim of this study is to gain insight into the nature of loneliness among school principals. The study employed a qualitative research design incorporating a phenomenological approach. The participants of the study consisted of seven elementary school principals. The data was collected via face-to-face interviews, and related observations were carried out over the duration of two months during the two semesters of the 2015-2016 academic year. The data was then analysed across three steps, namely an exploration of the general meaning/significance of the data, an encoding of the data, and a subsequent identification of the principal themes involved. As a result of this analysis, three main themes were identified: psychological insight, the organisational climate, and professional effort. Psychological insight is the notion that all participants agreed on and emphasised when asked to offer a definition of loneliness at schools. Participants also agreed on the fact that the organisational climate at Turkish schools represented the most significant reason for principals' loneliness at work. The school principals that participated in the study stated that they invested (additional) professional efforts (in their work) to overcome this invisible barrier. The results were discussed in the light of existing literature, and suggestions were presented within the context of the final discussion.
Keywords: barriers; loneliness at work; school principals; Turkish elementary schools; EMOTIONAL LONELINESS; WEISS TYPOLOGY; WORKPLACE; TOP; Education & Educational Research